Entender a crise, retomar as conquistas - Dowbor, Ladislau (Estudos Avançados, 2017)
Brazil's economy displayed exceptional economic growth and social inclusion between 2003 and 2013. Increased consumption at the bottom of the pyramid sped up private investment. This model works, as it worked during the "Golden 30s." In 2013, the model was attacked by the financial system, abetted by political opportunism, leading to the present crisis. The prime interest rate reached 156% (for an inflation of 6.5%) and interest on public sector debt reached 13%. One trillion reais, 15% of GDP, were taken out of the real economy. The main engines of the economy, family consumption, business investment, and public social policies and investment were stalled. Opportunities to go back to what works require control over the financial system, so that it serves, instead of draining, the real economy.